38. EVALUATION OF THE RESULTS OF LASER LAPAROSCOPIC TREATMENT OF URTERAL STONIC DISSOLUTION AT MILITARY HOSPITAL 91 PERIOD 2020 - 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the effectiveness and safety of endoscopic retrograde laser lithotripsy with arigid scope in the treatment of ureteral stones in 2020 - 2023.Subjects and methods: Prospective study describing intervention, performed on 256 patientsdiagnosed with ureteral stones in various locations, endoscopic retrograde laser lithotripsy at MilitaryHospital 91 from February 2020 to June 2023.Results: In the study, there were 49.6% right ureteral stones, 48.6% left ureteral stones, 2% bilateralureteral stones, 33.2% upper 1/3 stones, 30.2% middle 1/3 stones, 4%, stones in the lower third27.3%. The average size of the stones is 13.1mm, 90.2% of the stones are radiopaque, and 9.8% ofthe stones are not clearly visible. Stones cause ureteral obstruction in hydronephrosis level I in 18.3%,hydronephrosis level II in 72.6%, hydronephrosis level III in 8.9% and 0.2% of non-hydronephrosispatients; Average lithotripsy time is 36.2 minutes, 2.34% of stones cannot be reached; Indicationsfor JJ tube placement after stone intervention account for 100%.Conclusion: Retrograde ureteroscopy with a rigid scope and laser diffuser source has high value intreating ureteral stones, with 96% success. The method is safe, highly effective, shortens treatmentdays, and restores health early.
Keywords: Laser retrograde ureteral lithotripsy, 91 military Hospital